Protein DEK and DTA Aptamers: Insight Into the Interaction Mechanisms and the Computational Aptamer Design - Dai, Lijun; Zhang, Jiangnan; Wang, Xiaonan; Yang, Xiaoyue; Pan, Feng; Yang, Longhua; Zhao, Yongxing (Frontiers in Molecular Biosciences, 2022)
Through blocking DEK protein, DEK-targeted aptamer (DTA) can reduce the formation of neutrophil extracellular traps (NETs) to reveal strong anti-inflammatory efficacy in rheumatoid arthritis. However, the poor stability of DTA has greatly limited its clinical application. Thus, in order to design an aptamer with better stability, DTA was modified by methoxy groups (DTA_OMe) and then the exact DEK-DTA interaction mechanisms were explored through theoretical calculation. The corresponding 2’-OCH3-modified nucleotide force field was established and the molecular dynamics (MD) simulations were performed. It was proved that the 2’-OCH3-modification can enhance the stability of DTA on the premise of comparative affinity definitely. Further, the electrostatic interaction contributed the most to the binding of DEK-DTA, which was primary interaction to maintain the stability, in addition to the nonspecific interactions between positively-charged residues (eg. Lys and Arg) of DEK and negatively-charged phosphate backbone of aptamers. H-bond network analysis reminded eight bases could be mutated to enhance the affinity of DTA_OMe probably. Thereinto, replacing the 29th base from cytosine to thymine of DTA_OMe was theoretically confirmed to be with the best affinity and even better stability. These researches imply to be a promising new aptamer design strategy for the treatment of inflammatory arthritis.